The Influence of Customer Experience and Social Media Marketing on Customer Loyalty Through Customer Satisfaction at Teraseduh Medan - Samuel Morales Pandapotan Simanjuntak; Beby Karina Fawzeea Sembiring; Amlys Syahputra Silalahi (Indonesian Journal Publisher, 2026)
The coffee shop industry in Medan City has experienced significant growth, but faces challenges in maintaining customer loyalty. This study analyzes the influence of customer experience and social media marketing on customer loyalty through customer satisfaction at Teraseduh Medan, a coffee shop that experienced a decrease in visits from 680 visitors per day (2022) to 420 visitors (2024). Using a quantitative method with PLS-SEM analysis on 135 respondents selected through purposive sampling, data were collected through a structured questionnaire. The results showed that customer experience had a positive and significant effect on customer satisfaction (β=0.441, p=0.000) and customer loyalty (β=0.324, p=0.000). Social media marketing has a positive and significant effect on customer satisfaction (β=0.513, p=0.000) and customer loyalty (β=0.201, p=0.036). Customer satisfaction was proven to mediate the relationship between customer experience (β=0.146, p=0.002) and social media marketing (β=0.170, p=0.002) on customer loyalty, and showed the strongest direct influence on customer loyalty (β=0.331, p=0.000), explaining the 40.6% variance in customer loyalty decisions. These findings confirm that digital marketing strategies should be prioritized through consistent and authentic quality improvement of customer experiences, as well as the utilization of interactive social media content to strengthen satisfaction and drive customer loyalty in the specialty coffee industry.